2021
DOI: 10.1021/acs.inorgchem.0c03717
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Rare-Earth Metals and Some Perfluorinated β-Diketones

Abstract: In this work, we demonstrate the fundamental relationships between stability constants and periodic, acid–base, and structural parameters for complexes of some 1,3-diketones. The four analogues of hexafluoroacetylacetone2-thenoyltrifluoroacetone, 2-furoyltrifluoroacetone, benzoyltrifluoroacetone, and 2-naphthyltrifluoroacetonehave been studied as chelating ligands for 16 rare-earth metals (Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu) in aqueous solutions. Systems have been investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…When the excited triplet energy level of the ligand is higher than the 5 D 0 energy level of Eu, the energy transfer from ligand to Eu 3+ may occur and the fluorescence of Eu 3+ can be sensitized, which is called the “antenna effect” . It is reported that LVFX includes the β-diketone moiety which has a strong coordination ability with Eu 3+ . , When LVFX is added to free Eu 3+ , the fluorescence of Eu 3+ + LVFX is still weak, indicating that LVFX cannot replace water molecules coordinating with Eu 3+ and the ineffective energy transfer from LVFX to Eu 3+ (Figure A). However, the addition of LVFX into Eu@Am-MSNs causes great enhancement of red emission from Eu (Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the excited triplet energy level of the ligand is higher than the 5 D 0 energy level of Eu, the energy transfer from ligand to Eu 3+ may occur and the fluorescence of Eu 3+ can be sensitized, which is called the “antenna effect” . It is reported that LVFX includes the β-diketone moiety which has a strong coordination ability with Eu 3+ . , When LVFX is added to free Eu 3+ , the fluorescence of Eu 3+ + LVFX is still weak, indicating that LVFX cannot replace water molecules coordinating with Eu 3+ and the ineffective energy transfer from LVFX to Eu 3+ (Figure A). However, the addition of LVFX into Eu@Am-MSNs causes great enhancement of red emission from Eu (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…54 It is reported that LVFX includes the β-diketone moiety which has a strong coordination ability with Eu 3+ . 55,56 When LVFX is added to free Eu 3+ , the fluorescence of Eu 3+ + LVFX is still weak, indicating that LVFX cannot replace water molecules coordinating with Eu 3+ and the ineffective energy transfer from LVFX to Eu 3+ (Figure 5A). However, the addition of LVFX into Eu@Am-MSNs causes great enhancement of red emission from Eu (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…Yield: 0.45 g (18%); mp 101−103 °C; Raman (80 mW, in cm −1 ) ν: 3074 (38), 3064 (42), 3035 (15), 2987 (16), 2958 (46), 2923 (42), 2858 (35), 1598 (100), 1550 (9), 1527 (27), 1492 (13), 1438 (45), 1400 (32), 1371 (19), 1325 (22), 1300 (9), 1180 (6), 1161 (20), 1051 (10), 1024 (14), 1010 (11), 999 (61), 850 (15), 715 (9), 642 (18), 615 (15), 436 (6), 266 (6), 247 (6), 148 (11), 117 (13), 75 (74); IR (ATR, in cm −1 ) ν: 2955 (vw), 2856 (vw), 2490 (vw), 1599 (w), 1549 (m), 1531 (m), 1491 (w), 1460 (w), 1437 (w), 1400 (w), 1369 (vw), 1325 (w), 1298 (vw), 1265 (vw), 1188 (s), 1165 (m), 1092 (w), 1070 (w), 1051 (w), 1011 (vs), 924 (vw), 833 (w), 804 (vs), 768 (s), 712 (m), 692 (s), 654 (w), 642 (vw), 607 (m), 552 (vs), 511 (m), 434 (m); 1 H NMR (CDCl 3 , 300 K, in ppm): δ 2.26 (3H, d, 4 J HP = 0.8 Hz, H4), 3.76 (6H, d, 3 J HP = 11.7 Hz, H5), 7.28 (1H, mt, 3 J HH = 7.5 Hz, H10), 7.43 (2H, mt, 3 J HH = 8.0 Hz, H9), 7.77 (2H, md, 3 J HH = 7.6 Hz, H8); 13 C{ 1 H} NMR (CDCl 3 , 300 K, in ppm): δ 14.0 (1C, s, C4), 52.9 (2C, d, 2 J CP = 5 Hz, C5), 82.6 (1C, d, 1 J CP = 219 Hz, C2), 121.5 (2C, s, C8), 126.8 (1C, s, C10), 129.2 (2C, s, C9), 137.8 (1C, s, C7), 149.6 (1C, d, 2 J CP = 10 Hz, C3), 159.8 (1C, d, 2 J CP = 23 Hz, C1); 31 (2-ethylhexyl)(5-hydroxy-3-methyl-1-phenyl-1H-pyrazol-4-yl)phosphonate HL 3 .…”
Section: Synthesis Of Dimethyl(5-hydroxy-3-methyl-1phenyl-1hpyrazol-4...mentioning
confidence: 99%
“…Yield: 0.12 g (4%); mp 113−115 °C; Raman (255 mW, in cm −1 ) ν: 3068 (100), 3031 (16), 2937 (30), 1597 (54), 1502 (15), 1406 (18), 1371 (13), 1280 (14), 1222 (12), 1006 (30), 87 (36), 75 (32), 63 (39), 52 (66); IR (ATR, in cm −1 ) ν: 3064 (vw), 2924 (vw), 2785 (vw, br), 2586 (vw), 1626 (w), 1591 (w), 1549 (w), 1500 (w), 1487 (m), 1458 (w), 1400 (w), 1369 (vw), 1352 (vw), 1311 (w), 1281 (vw), 1252 (w), 1209 (w), 1186 (m), 1159 (w), 1072 (vw), 1022 (vw), 930 (w), 914 (m), 897 (m), 839 (w), 773 (m), 764 (m), 742 (w), 725 (w), 710 (w), 687 (m), 625 (vw), 615 (vw), 588 (w), 563 (w), 548 (w), 530 (w), 513 (w), 492 (w), 484 (w); 1 H NMR (CDCl 3 , 300 K, in ppm): δ 2.37 (3H, s, H4), 7.20 (2H, t, 3 J HH = 7.2 Hz, H8), 7.23 (4H, d, 3 J HH = 7.8 Hz, H6), 7.28 (1H, t, 3 J HH = 7.5 Hz, H13), 7.35 (4H, t, 3 J HH = 7.8 Hz, H7), 7.42 (2H, t, 3 J HH = 7.8 Hz, H12), 7.74 (2H, d, 3 J HH = 8.0 Hz, H11); 13 recently, and the characterization data was also reported. 69 HL 8 was recently reported by our group, and its preparation was reproduced in this work.…”
Section: Synthesis Of Dimethyl(5-hydroxy-3-methyl-1phenyl-1hpyrazol-4...mentioning
confidence: 99%
See 1 more Smart Citation